2022
DOI: 10.3390/nu14071462
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity across the Life-Course and Cognitive Function among Older Mexican Adults

Abstract: Background: Food insecurity remains a global public health problem. Experiencing food insecurity is related to poorer cognitive function among older adults. However, few studies have examined how food insecurity, experienced over the life-course, relates to cognitive function among older adults in Mexico. Methods: Data came from the 2015 Mexican Health and Aging Study (n = 11,507 adults aged 50 and over). Early- and late-life food insecurity were ascertained by self-report. We evaluated how both measures of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…In the lifecourse epidemiology literature, early life FI (or more specifically, undernutrition) is considered one of the many potential adverse conditions that contribute to health outcomes later in life (Ben‐Shlomo & Kuh, 2002; Kuh et al, 2003). Saenz et al (2022) found that FI in childhood is related to poorer cognitive function in adulthood. While stress and its effects on brain development and structure have been implicated as the mechanism tying FI to cognitive health outcomes, these factors may also contribute to poorer sleep which, in turn, may exacerbate mental and physical health concerns.…”
Section: Discussionmentioning
confidence: 99%
“…In the lifecourse epidemiology literature, early life FI (or more specifically, undernutrition) is considered one of the many potential adverse conditions that contribute to health outcomes later in life (Ben‐Shlomo & Kuh, 2002; Kuh et al, 2003). Saenz et al (2022) found that FI in childhood is related to poorer cognitive function in adulthood. While stress and its effects on brain development and structure have been implicated as the mechanism tying FI to cognitive health outcomes, these factors may also contribute to poorer sleep which, in turn, may exacerbate mental and physical health concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Further information on the MHAS cognitive measures is available in other work [ 63 , 64 ]. Although other cognitive tasks have been assessed in the MHAS, we focus on these four as these measure cognitive domains that have been previously assessed in relation to food insecurity such as memory and executive function [ 28 , 29 , 31 ]. These tasks also do not require mathematical or literacy abilities, which is essential in evaluations of cognition in settings with lower formal education levels.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work has suggested that food insecurity may also negatively impact the brain and cognitive function [ 21 , 22 ]. Studies have reported effects of food insecurity on outcomes spanning lower cognitive function [ 23 29 ], faster cognitive decline [ 30 32 ], mild cognitive impairment [ 33 37 ], and dementia [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations